Attributional Styles and Their Impact on Depressive and Anxious Symptoms in Italian Children: Insights from the Italian Children’s Attributional Style Questionnaire-Revised (CASQ-R) - Simona Scaini; Silvia Grazioli; Ludovica Giani; Barbara Forresi; Stefano De Francesco; Marcella Caputi (Pediatric Reports)
Background: There is evidence that the tendency to adopt a peculiar pattern of causal inference, known as attributional style, is likely related to specific patterns of psychopathology among youth. Objective: This study aims to assess preliminary psychometric properties of the Italian Children’s Attributional Style Questionnaire-Revised (CASQ-R) and to explore the presence of any subgroups of children and early adolescents from the general population who might exhibit internally homogeneous and externally heterogeneous attributional styles through latent class analysis, delving into the potential sociodemographic, namely age and gender, and clinical differences among the identified classes of attributional styles. Method: A sample of 337 children (11.29 ± 1.76 years old, 169 females, and 168 males) was recruited and their attributional styles and depressive and anxious symptoms were analyzed. Results: Two distinct classes were defined using the CASQ-R items in a latent class analysis (LCA). In particular, high levels of depressive (Kruskal–Wallis chi-squared = 9.37, df = 1, Bonferroni-adjusted p = 0.002) and school phobia (Kruskal–Wallis chi-squared = 7.17 df = 1, Bonferroni-adjusted p = 0.037) symptoms were reported by children showing an internal, global and stable attributional style for negative events and an external, specific and unstable attributional style for positive events. Conversely, low levels of depressive and school phobia symptoms were reported by children showing the opposite attributional style. Conclusions: The identified classes shed light on distinct patterns associated with depressive and anxious symptoms, offering potential insights for targeted interventions.